PENGARUH UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP TINDAKAN PENGHINDARAN PAJAK (TAX AVOIDANCE) PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hernadianto Hernadianto; Ahmad Junaidi; Agus Dwi Prayogi (Universitas Muhammadiyah Bengkulu, 2020)
ABSTRACTTax avoidance is a way to avoid paying taxes legally by taxpayers by reducing the amount of tax owed without violating tax rules or in other terms looking for regulatory weaknesses. Executives have a significant positive role in tax avoidance. The purpose of this study was to determine the effect of company size and leverage on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. This study the type of this research can be classified into empirical research. The data used in this study were secondary data from companies listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that variable Size of the company does not affect tax avoidance. The size of the company will not affect tax avoidance. Every company management wants to be assessed as good by shareholders so that small or large companies will do tax avoidance. Leverage variables have a significant positive effect on tax avoidance. The higher the level of leverage obtained by the company, the higher the level of tax avoidance by the company.Â Keywords: Company size, leverage, tax avoidance, manufacturing companiesÂ